Prognostic scores for sorafenib-treated hepatocellular carcinoma patients: A new application for the hepatoma arterial embolisation prognostic score. (November 2017) - Edeline, J.; Blanc, J.-F.; Campillo-Gimenez, B.; Ma, Y.-T.; King, J.; Faluyi, O.; Mathurin, J.; Ghazi, S.; Palmer, D.H.; Meyer, T.
Abstract: Background: No prognostic classification is currently used for patients treated with systemic therapies for Hepatocellular Carcinoma (HCC). Methods: We retrospectively analysed data from patients treated with sorafenib for HCC from five centres in France and in the United Kingdom (UK). The training set comprised data from two centres and the validation set from three. Variables independently associated with Overall Survival (OS) in the training set were used to build the SAP (Sorafenib Advanced HCC Prognosis) score. The score was tested in the validation set, then compared with other prognostication systems. Results: The training set and validation set included 370 and 468 patients respectively. In the training set, variables independently associated with OS in multivariable analysis were: performance status (PS) >0, alpha-fetoprotein (AFP) >400 ng/ml, tumour size >7 cm, bilirubin >17 μmol/l and albumin <36 g/l. The SAP score was built giving one point to each abnormal variable, and three classes were constructed. The SAP score was significantly associated with OS in the training set, with median OS of 14.9 months for SAP A, 7.2 months for SAP B and 2.5 months for SAP C ( P < 0.001). In the validation set, the SAP score was significantly associated with OS, and showed greater discriminative abilities than Barcelona Clinic Liver Cancer (BCLC) and albumin-bilirubin (ALBI) scores. However, the hepatoma arterial embolisation prognostic (HAP) score showed greater discriminative abilities than the SAP score. Conclusion: In European patients treated with sorafenib, the HAP was the most discriminant prognostic score and may facilitate stratification in trials and inform clinical decision making. Highlights: We studied a training set of 370 patients treated with sorafenib for HCC. Variables associated with OS were PS, AFP, tumor size, bilirubin and albumin. We designed a new prognostic model and validated it in a cohort of 468 patients. However, the HAP score was the most discriminant model in the validation cohort. The HAP score could be thus used as a prognostic model in this population.